The immunobiology and therapeutic potential of regulatory T cells in autoimmune diseases and allergic diseases - Xie, Wen-Wen; Huang, Jian-Bin; Zhou, Yi-Chi; Yuan, Jing-Yi; Feng, Jia-Xue; Shi, Xiao-Hang; Tian, Li; Zeng, Xian-Hai; Qiu, Shu-Qi; Zhao, Mei-Zhen; Cheng, Bao-Hui; Zeng, Hao-Tao (Frontiers in Immunology, 2026)
Autoimmune and allergic diseases represent two major categories of immune-mediated disorders that collectively impose a significant global health burden. Although driven by distinct triggers—aberrant responses against self-antigens in autoimmunity and hypersensitivity to innocuous environmental antigens in allergy—both classes of disease are fundamentally rooted in a failure of immunological tolerance. At the center of this regulatory failure lies the dysfunction of regulatory T cells (Tregs) which are the master orchestrators of peripheral tolerance, actively suppressing effector immune responses through the secretion of inhibitory cytokines and contact-dependent inhibition. In both autoimmune and allergic conditions, defects in Treg number, stability, or suppressive function permit the uncontrolled expansion of autoreactive lymphocytes in autoimmunity, while in allergic diseases, it fails to constrain the T helper 2 (Th2) cell-mediated pathways that drive pathology. Despite the well-established role of Tregs in each disease category, research often proceeds in parallel, leaving a critical knowledge gap regarding the convergent mechanisms of Treg failure across these interconnected pathologies. A unified understanding of how factors such as genetic predispositions and environmental influences cohesively impact Treg function remains underdeveloped. This review addresses this gap by providing a comprehensive synthesis of Treg immunobiology, with a specific emphasis on the convergent pathways that underpin their dysfunction in both autoimmune and allergic diseases. By elucidating the shared principles of Treg-mediated immune dysregulation, this review aims to provide a robust conceptual framework to accelerate the development of next-generation therapies capable of restoring tolerance across this broad spectrum of disorders.